DESIGN AND SYSEM OF A BOARDING HOUSE MAPPING LOCATION - Chandra JE Sihombing; Sandi Darmo Winoto (President University, 2022)
Lack of facilities to obtain informationabout boarding houses is one of the problems often facedby immigrants. The majority who occupy the boardinghouse are students or workers who come from outsidethe area, so to determine the ideal boarding house,considerations about apart from facilities and price, thedistance from the boarding house to the location is alsoone of the considerations for choosing a boarding house.Therefore, a web-based Info Boarding application wasmade using the google maps API. The process of makingthis web using the PHP programming language, usingXAMPP (PHPMyAdmin) for database creation, usingthe google maps API to display google maps on thewebsite as a base map. information about boardingfeatures, booking features, and filter features topredetermined locations. With this website-basedapplication, it is hoped that it will make it easier forpeople to find boarding houses according to user needs